Biomaterial modification of urinary catheters with antimicrobials to give long-term broadspectrum antibiofilm activity - Fisher, Leanne E.; Hook, Andrew L.; Ashraf, Waheed; Yousef, Anfal; Barrett, David A.; Scurr, David J.; Chen, Xinyong; Smith, Emily F.; Fay, Michael; Parmenter, Christopher D.J.; Parkinson, Richard; Bayston, Roger (Elsevier, 2015)
Catheter-associated urinary tract infection (CAUTI) is the commonest hospital-acquired infection, accounting for over 100,000 hospital admissions within the USA annually. Biomaterials and processes intended to reduce the risk of bacterial colonization of the catheters for long-term users have not been successful, mainly because of the need for long duration of activity in flow conditions. Here we report the results of impregnation of urinary catheters with a combination of rifampicin, sparfloxacin and triclosan. In flow experiments, the antimicrobial catheters were able to prevent colonization by common uropathogens Proteus mirabilis, Staphylococcus aureus and Escherichia coli for 7 to 12 weeks in vitro compared with 1–3 days for other, commercially available antimicrobial catheters currently used clinically. Resistance development was minimized by careful choice of antimicrobial combinations. Drug release profiles and distribution in the polymer, and surface analysis were also carried out and the process had no deleterious effect on the mechanical performance of the catheter or its balloon. The antimicrobial catheter therefore offers for the first time a means of reducing infection and its complications in long-term urinary catheter users.